Desain Koalisi Permanen Partai Politik dalam Sistem Pemerintahan Indonesia - Siboy, Ahmad (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
The pattern of political party coalitions that fluctuate ahead of the general election indicates that the coalitions are not built based on substantial interests but pragmatic interests. As a result, the status of each party becomes unclear, which one acts on the side of the government and which one acts as the opposition. This study aims to discuss the options of permanent coalition patterns that can be applied. The research problem of this study was â€œWhat is the permanent coalition design that can be applied in the Indonesian government system?â€. This study used normative legal research with statutory, conceptual, and case-study approaches. The results indicated that a permanent coalition is needed to strengthen the coalition pattern of political parties as a support for the Indonesian government system. The permanent coalition design that can be applied is a two-pole model, in which there will only two coalition groups of political parties: parties supporting the government and parties opposing the government. This two-pole model can be balanced in terms of the power between a coalition of government parties and a coalition of opposition parties. Another design that can be adopted is the coalitions which are established based on the similarity of the ideology of each political party.